Passive and active approaches to tackle antifouling - Gaw, Sheng Long (2019)
Biofouling is the accumulation of unwanted organisms on a surface. Biomedical and marine industries are of are two main particular interest for this study. Biofouling in marine industry reduces the performance of the equipment, leading to an increase in operating cost and downtime. In the medical industry, it can lead to catastrophic effects on the patient and might lead to death in the event of bacterial infection. Till date, there is no absolute solution to this problem. Therefore, this study provides a valuable contribution to the community by providing three novel antifouling methods.